A humánfejlettség és a szociokulturális háttér hatása a középiskolai eredményesség területi mutatóira - Győri, Ferenc (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
As it has been proven by a lot of studies our career chances as well as our development mostly depend on the educational background. A factor of great importance in the process of talent development is the school. The destiny of the talented is basically influenced by their social circumstances. It gave me the idea to find relations between rates of achieve-ment at school (result of entrance exams and of national competitions) and human devel-opment index (HDI) which expresses the social and territorial differences. The most im-portant result is the level of human development influences the competition achievements in a stronger way than the results of entrance exams at colleges and universities.